(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the satisfaction of pregnant women and their relatives using the family delivery service package at the Department of Obstetrics, National Hospital of Obstetric and Gynecology. Method: A cross-sectional descriptive study, collected on 252 pregnant women who registered for normal delivery at the Department of Obstetrics, National Hospital of Obstetric and Gynecology and used the family delivery service package from July 15, 2024 to August 31, 2024. The collected data were entered and analyzed using SPSS 16.0 software. Results: First-time mothers accounted for 66.7%; mothers who had perineal sutures accounted for 99.2%; mothers who received pain relief during labor with medication accounted for 79.4%. Pregnant women and their families were satisfied with the ability to access family delivery services in terms of the department’s facilities as well as the attitudes and professional competence of medical staff. Conclusions: Maternal and their families were satisfied with the family delivery service package, the department’s facilities as well as the attitudes and professional competence of medical staff.